Pilot plant study of recovery of lactic acid from ethyl lactate - Barve, Prashant P.; Rahman, Imran; Kulkarni, Bhaskar D. (Organic Process Research & Development, 2009)
Purified lactic acid is used for production of biodegradable polymer. Esterification with ethanol and subsequent hydrolysis in distillation columns to produce purified lactic acid without catalyst has obvious advantages. In this paper, we present a pilot-plant study of ethyl lactate hydrolysis to produce 3.86 kg/h lactic acid (99.85% purity) using three distillation columns. Simulation of distillation columns at steady state has been carried out, and the results obtained tally with the experimental results of the pilot plant.